Tiger Woods drive to greatness - Stewart, Mark (Millbrook Press, 2001)
A heavily illustrated biography of the young professional golfer whose winning ways have won the respect of the PGA and the hearts of millions. His extraordinary 1999 and 2000 seasons are chronicled, including the 1999 PGA Championship and 2000 Masters Tournament. An up-to-date look at the life of this incredibly well-known and well-liked personality.